AFFECTING FACTORS IN EMPLOYEE PERFORMANCE KOTO BARU SUB-DISTRICT, DHARMASRAYA DISTRICT - Selamat, Selamat; Heryanto, Heryanto (Archives of Business Research, 2019)
The purpose of this study was to 1) examine the influence of communication on employee work motivation in Koto Baru Subdistrict, Dharmasraya District, 2) examine the influence of the work environment on employee work motivation in Koto Baru Subdistrict, Dharmasraya Regency, 3) Test the influence of communication on employee performance in Koto Baru Subdistrict Dharmasraya District, 4) Test the influence of work environment on employee performance in Koto Baru Subdistrict, Dharmasraya Regency, 5) Test the effect of work motivation on employee performance in Koto Baru Subdistrict, Dharmasraya Regency, 6) Test the effect of work motivation as an intervening variable between communication and employee performance in Koto Baru Subdistrict Dharmasraya District , 7) Examining the effect of work motivation as an intervening variable between work environment and employee performance in Koto Baru District, Dharmasraya Regency. The type of this research is Expost-Facto, the population of the study is all of the employees of Koto Baru Subdistrict, Dharmasraya Regency, as many as 81 people, the sampling technique is total sampling, where the number of samples is 81 employees of Koto Baru Sub-District, Dharmasraya Regency. The analysis technique used is path analysis. The results of this study indicate that 1)) Communication has a positive and significant effect on employee work motivation in Koto Baru Subdistrict, Dharmasraya Regency, 2) The work environment has a positive and significant effect on the work motivation of employees in Koto Baru Subdistrict, Dharmasraya Regency, 3) Communication has a positive and significant effect on performance employee of Koto Baru Subdistrict, Dharmasraya Regency, 4) The work environment has a positive and significant effect on the performance of employees of Koto Baru Subdistrict, Dharmasraya District, 5) Work motivation has a positive and significant effect on the performance of employees of Koto Baru Subdistrict, Dharmasraya Regency, 6) Work motivation as an intervening variable has a significant effect between communication and performance performance of the employees of Koto Baru Subdistrict, Dharmasraya Regency, direct and indirect effects were obtained at 9.54%, 7) Work motivation as an intervening variable had a significant effect between work environment and employee performance performance Koto Baru sub-district, Dharmasraya Regency. the calculation of direct and indirect influence is obtained at 8.33%.